Coping with course delivery in Singapore [Teaching in an era of Covid-19 pandemic] - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2020)
It was like swimming against the tide. Slowly but surely, as Covid-19 began to engulf the world, the inevitability of having to transit to online teaching loomed closer by the day. When the threat became more severe by the end of March, we were told we had to go online.